Acute swimming exercise, but not exposure to moderate hypoxic conditions reduces circulating selenoprotein P levels in short-term, high-fat diet-fed rats - Shohei Dobashi; Arisa Nakamura; Kyohei Saito; Daisuke Ando; Katsuhiro Koyama (Japanese Society of Physical Fitness and Sports Medicine, 2019)
The purpose of this study was to investigate the impact of acute exercise and hypoxic exposure on the level of circulating selenoprotein P (SeP), which is known to cause insulin and exercise resistance, and expression of the muscle peroxisome proliferator-activated receptor-γ co-activator-1α (PGC-1α) gene in pre-diabetes rat models. Fifteen week old male Wistar rats (n = 20) were fed with a high-fat diet and water ad libitum for 3 weeks. After the acclimation period, they were assigned to sedentary or exercise groups under normoxic (20.9% O2) and hypoxic (14.5% O2) conditions. Each of the exercise groups (NE and HE) was administered two 30-min no-load swimming exercises with an interval of 5-min rest. The serum, the liver, and the triceps muscle were obtained 3 h after the exercises. Hypoxic exposure did not affect hepatic SeP mRNA, serum SeP protein, and muscle PGC-1α mRNA expression. In contrast, acute swimming exercise reduced circulating SeP concentration and increased PGC-1α mRNA expression in triceps muscle. In conclusion, acute swimming exercise rather than moderate hypoxic exposure might improve insulin and exercise resistance in pre-diabetes conditions for type 2 diabetes.